Substance use among serious adolescent offenders following different patterns of antisocial activity. - Besana, Michelle; Mulvey, Edward P. (2011)
The present study examines individual differences in the levels of substance use in a sample (n=1,067) of male serious adolescent offenders following distinct trajectories of criminal offending over a three year period. The levels of substance use are compared for the different offender groups controlling the effects of age, ethnicity, and diagnosis of previous drug and alcohol abuse/dependence. The association between antisocial activity and the level of substance use was also examined and compared for the different groups after controlling the effect of institutional placement. The growth or decline in substance use was investigated and compared for the different groups above and beyond the effects of antisocial activity and institutional confinement.

After fitting a series of hierarchical generalized linear models for repeated measurements data, results revealed that significant differences in the level of substance use exist among the different offender groups in the sample. Antisocial activity is associated with the level of substance use over time after controlling the effect of institutional placement in all offender groups in the sample. Antisocial activity is associated with the level of substance use over time after controlling the effect of institutional placement in all offender groups. Above and beyond the effect of antisocial activity and institutional placement, substance use is increasing over the data collection period in all groups, but the rate of growth is highest in the lowest offending group.
Keywords: Juvenile delinquents; Generalized linear models; Juvenile delinquency -- Philippines